2016
DOI: 10.1523/jneurosci.3235-15.2016
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Asymmetry in Dark–Bright Processing Initiates Propagating Activity across Primary Visual Cortex

Abstract: Differences between visual pathways representing darks and lights have been shown to affect spatial resolution and detection timing. Both psychophysical and physiological studies suggest an underlying retinal origin with amplification in primary visual cortex (V1). Here we show that temporal asymmetries in the processing of darks and lights create motion in terms of propagating activity across V1. Exploiting the high spatiotemporal resolution of voltage-sensitive dye imaging, we captured population responses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 106 publications
5
39
0
Order By: Relevance
“…However perceived contrast of decremental gratings were not systematically studied previously under conditions similar to those reported here. Processing differences between positive and negative local contrast has been reported in literature both by behavioral and neuronal studies (e.g., Chubb & Nam, 2000;Rekauzke et al, 2016;Rudd & Zemach, 2004Sato et al, 2016;Whittle, 1986;Zaghloul et al, 2003). The light-dark asymmetry is also incorporated in some models of brightness (e.g., Rudd, 2013Rudd, , 2014.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…However perceived contrast of decremental gratings were not systematically studied previously under conditions similar to those reported here. Processing differences between positive and negative local contrast has been reported in literature both by behavioral and neuronal studies (e.g., Chubb & Nam, 2000;Rekauzke et al, 2016;Rudd & Zemach, 2004Sato et al, 2016;Whittle, 1986;Zaghloul et al, 2003). The light-dark asymmetry is also incorporated in some models of brightness (e.g., Rudd, 2013Rudd, , 2014.…”
Section: Discussionmentioning
confidence: 96%
“…4). Using rectified gratings allowed us to study positive and negative contrast patterns independently, which was critical because both behavioral and neural evidence in previous studies suggest fundamental differences between processing of incremental and decremental luminance patterns (e.g., Blackwell, 1946;Chubb & Nam, 2000;Economou, Zdravkovic, & Gilchrist, 2007;Kremkow, Jin, Wang, & Alonso, 2016;Patel & Jones, 1968;Rekauzke et al, 2016;Rudd & Zemach, 2004Sato, Motoyoshi, & Sato, 2016;Whittle, 1986;Zaghloul, Boahen, & Demb, 2003). Previous studies in literature have found interactions between spatial frequency and mean luminance in contrast perception using simple gratings (Chubb, Sperling, & Solomon, 1989;Georgeson & Sullivan, 1975;Peli et al, 1996;Robilotto & Zaidi, 2004;Van & Bouman, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…[118][119][120] Here, two examples in the visual domain were presented, where propagation of cortical activity emerges from local spacetime imbalances in the computation of external input. 20,21 The crucial factor for both instances is that local input creates cortical spread, which builds up a gradient of activity-from subthreshold to suprathreshold levels. The initial temporal advance in the generation of precuing activity enables subsequent input to boost asymmetric propagation of suprathreshold activity in V1.…”
Section: Discussionmentioning
confidence: 99%
“…In support of this idea, we recently showedusing another paradigm that creates apparent motion perception in humans-how asymmetrically propagating activity resembles the perceived direction of motion. 21 Once again, the high spatiotemporal resolution of VSDI enabled us to track activity Histological section of cortical tissue after staining with cytochrome oxidase that visualizes the regular mosaic pattern of oxidase blobs in V1 (Macaque monkey). The small square in the center of the image approximates the region that is activated by feedforward thalamic input using a visual stimulus as small as 0.5 deg × 0.25 deg in size.…”
Section: -16mentioning
confidence: 99%
See 1 more Smart Citation